Slant PAF helices for PAFs of non-null curves in three-dimensional Minkowski space M13 - Bektas, Mehmet (World Scientific Publ Co Pte Ltd, 2025)
The aim of this study is to investigate the types of Positional Adapted Frame (PAF) helices (slant PAF helices), which are also very useful for both physicians and mathematicians, on these three types of PAF.
Keywords: Slant PAF helices; PAF